Bankruptcy Law, Creditors' Rights and Contractual Exchange in Europe, 1808-1914 - Jérôme Sgard (Oesterreichische Nationalbank (OeNB), 2006)
Recent historical research on bankruptcy has been centred almost exclusively on Common law countries, especially the United States. The consequence is that the research agenda includes issues which may, or may not, have broader relevance. This paper is an attempt at including within a larger historical and comparative perspective the evolution observed in continental Europe, during the 19th century. A data set has thus been assembled which includes the main features of a total of 51 codes or statutes, in 15 countries of all legal traditions. An early conclusion is that all these laws defended strongly creditors' rights during bankruptcy, during the whole period under review. This goes against the thesis defended i.a. by La Porta et alii (1998) which state that "legal origins" have a strong, differentiated effect on property and creditors' rights, which would be permanent over history. Two dimensions are then analysed. First, the status of the failed debtor, and whether he was subjected to repression; second, the degree to which the law supported or not the attempts of the parties to negotiate a composition, or continuation arrangement. An early period witnessed repressive, highly regulated frameworks: the paradigm is the Napoleonic, 1808 Code de commerce, though its main features were still highly visible half a century latter, in almost all countries. Then emerged a liberal model, between 1865 and 1885 with again a fair degree of convergence: the personal and civic fate of the debtor became much more immune to commercial failure; and the parties get more autonomy to bargain, though a bifurcation emerged between a "menu approach" to re-negotiation in England and in the French law countries, and a "single-option" procedure in German law countries. Beyond, it is proposed that these broad trends reflect the growing capacity of the institutional environment to reduce risks of moral hazards, and more generally transaction costs. By the end of the century, bargaining on bankruptcy had become easier and safer, so that judicial guarantees could be eased.
Keywords: 330